Speech Intelligibility and Personality Peer-ratings of Young Adults With Cochlear Implants - Freeman, Valerie (J Deaf Stud Deaf Educ, 2018)
Speech intelligibility, or how well a speaker’s words are understood by others, affects listeners’ judgments of the speaker’s competence and personality. Deaf cochlear implant (CI) users vary widely in speech intelligibility, and their speech may have a noticeable “deaf” quality, both of which could evoke negative stereotypes or judgments from peers. In this study, college students with typical hearing (TH) used semantic differential scales to rate speech samples of highly-intelligible TH young adults and age-matched CI users with high or low intelligibility (CI-Hi, CI-Lo) on personality traits related to competence (intelligence, achievement), friendship skills (friendliness, popularity), and attractiveness as a friend (extraversion, dependability). Judges rated TH positively, CI-Lo negatively, and CI-Hi as intermediate, even though CI-Hi were as intelligible as TH. Both CI user groups were rated as friendly but unattractive as friends (insecure, shy, boring, unpopular, does not “sound like someone who could be my friend”), underlining the role of deaf speech quality in peer judgments. Such negative first impressions are likely to affect CI users’ social interactions and friendships, highlighting the importance of speech intelligibility and quality for CI users and calling for education on deafness and deaf speech for TH peers.